Use of chitosan and tannins as alternatives to antibiotics to control mold growth on PDO Pecorino Toscano cheese rind. (December 2020) - Agnolucci, Monica; Daghio, Matteo; Mannelli, Federica; Secci, Giulia; Cristani, Caterina; Palla, Michela; Giannerini, Fabiola; Giovannetti, Manuela; Buccioni, Arianna
Abstract: The fungal microbiota usually growing on the cheese surface during ripening processes promote rind formation and the development of organoleptic characteristics, imparting positive sensory attributes to cheeses. As cheese contamination may also occur by undesirable molds, specific actions for preventing their growth are usually realized in dairy industries by using the antibiotic natamycin, which may represent a risk factor for human health and environmental sustainability. Here, agroindustrial by-products with natural antimicrobial properties, i.e. tannins and chitosan, were tested in a cheese-making trial producing PDO Tuscan pecorino cheese. Morphological and molecular methods revealed that the main components of rind fungal communities of PDO Tuscan pecorino cheese were represented by P. solitum, P. discolour and P. verrucosum . The use of chitosan on cheese rinds did not significantly affect the composition of rind fungal communities developing during the whole ripening process compared with controls treated with natamycin, whose numbers ranged from 3.4 ± 1.3 × 10 3 to 3.2 ± 1.8 × 10 4 and from 6.3 ± 3.5 × 10 2 to 4.0 ± 1.5 × 10 4, respectively. Overall, grape marc tannins and chitosan did not significantly affect the number and composition of fungal communities developing during PDO Pecorino Toscano cheese ripening, as well as its physical, chemical and nutritional profiles, showing that they may represent effective alternatives to the antibiotic natamycin. Highlights: The mycobiota of PDO Pecorino Toscano cheese was studied using a polyphasic approach. Rind fungal community was mainly represented by P. solitum, P. discolour and P. verrucosum . Fungal composition was not affected by grape marc tannins and chitosan rind treatments. Rind treatments did not affect cheese physical, chemical and nutritional profiles. Grape marc tannins and chitosan represent potential alternatives to natamycin.